EFEKTIVITAS PENDIDIKAN KESEHATAN TENTANG KEJANG DEMAM TERHADAP SIKAP ORANG TUA DALAM PENANGANAN KEGAWATDARURATAN KEJANG DEMAM PADA ANAK DI BANJAR BINOH KELOD DESA UBUNG KAJA - Sagung Mirah Purnama Dewi; Inca Buntari Agustini; Nadya Treesna Wulansari (Institute Teknologi dan Kesehatan (ITEKES) Bali, 2019)
The first treatment of febrile seizures in children is very important. Excessive worries and anxiety can be caused by education or knowledge of parents who are still less about the incidence of febrile seizures in children. This shows that much needed additional education about how the attitude of parents in handling emergency seizures in children fever. The goal is to know the effectiveness of health education about febrile seizures in the attitude of parents in handling emergency seizures in children in Banjar Binoh Kelod Ubung Kaja Village. This research uses pre-experimental design with one group pre test post test approach. The population in this study is all parents who have children aged under 5 years with a sample size of 20 respondents. The sampling technique used in this study is saturated sampling. Data collection tool used in this study is a questionnaire about parental attitudes in handling emergency seizures in children fever. The result of data analysis using Wilcoxon Sign Rank Test with significance level ɑ = 0,05 got result p value 0,000 which mean effective education of health toward parent attitude in handling emergency seizures in child fever. In this study, one that affects the attitude of parents in handling emergency spasmodic seizures in children is emotional. Confidence and good parental emotional levels are expected to improve parental attitudes in handling emergency seizures in children.